2001
DOI: 10.1128/jvi.75.9.4103-4109.2001
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus of Marine Mammals: a New Alphavirus Isolated from the Elephant Seal Louse, Lepidophthirus macrorhini

Abstract: A novel alphavirus was isolated from the louse Lepidophthirus macrorhini, collected from southern elephant seals, Mirounga leonina, on Macquarie Island, Australia. The virus displayed classic alphavirus ultrastructure and appeared to be serologically different from known Australasian alphaviruses. Nearly all Macquarie Island elephant seals tested had neutralizing antibodies against the virus, but no virus-associated pathology has been identified. Antarctic Division personnel who have worked extensively with el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
69
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 32 publications
1
69
0
1
Order By: Relevance
“…Additional work is required to confirm this preliminary finding, particularly in light of the poor specific antibody response typically observed in gadoids to infectious agents (Samuelsen et al 2006) Although insect vectors have not been identified for SAV, they form an important part of the epidemiology of other alphavirus infections (Walton et al 1973, Bowers et al 1995. Recently, the elephant seal louse Lepidophthirus macrorhini has been proposed as the vector for the newly identified alphavirus named southern elephant seal virus (SESV) (La Linn et al 2001). It can be speculated that the high levels of Caligus sp.…”
Section: Discussionmentioning
confidence: 96%
“…Additional work is required to confirm this preliminary finding, particularly in light of the poor specific antibody response typically observed in gadoids to infectious agents (Samuelsen et al 2006) Although insect vectors have not been identified for SAV, they form an important part of the epidemiology of other alphavirus infections (Walton et al 1973, Bowers et al 1995. Recently, the elephant seal louse Lepidophthirus macrorhini has been proposed as the vector for the newly identified alphavirus named southern elephant seal virus (SESV) (La Linn et al 2001). It can be speculated that the high levels of Caligus sp.…”
Section: Discussionmentioning
confidence: 96%
“…Last, the aquatic alphaviruses comprise two groups, Southern elephant seal virus and salmon pancreas disease virus (SPDV) (6,7). SPDV and its subtype sleeping disease virus are distantly related to all other alphaviruses (7).…”
mentioning
confidence: 99%
“…Alphaviruses infect a wide range of vertebrate and insect hosts, including mosquito species encompassing at least six genera as well as ticks and lice (6,(8)(9)(10). Vertebrate hosts include fish, equids, birds, amphibians, reptiles, rodents, pigs, humans, and nonhuman primates (9).…”
mentioning
confidence: 99%
“…Parasitic lice have been implicated in the transmission of the newly discovered southern elephant seal alphavirus (SESV) from the coast of Australia. SESV has been grouped genetically with the Semliki Forest virus complex (32).…”
mentioning
confidence: 99%